An Analysis of Patterns and Trends in United States Stormwater Utility Systems1. (29th September 2016) - Kea, Kandace; Dymond, Randel; Campbell, Warren
Abstract: Several factors, such as municipality location and population, are thought to influence trends among stormwater utilities (SWUs); however, no analysis of the relationship between these factors and SWU characteristics has been performed. This article corroborates hypothesized relationships and identifies trends and patterns in the establishment, funding mechanism, and magnitude of SWUs by analyzing location, population density, home value, and year of establishment for a comprehensive national SWU database with data for 1, 490 SWUs. The equivalent residential unit (ERU), a SWU that charges based on impervious area, was the most prevalent funding mechanism in all National Oceanic and Atmospheric Administration Climate Regions of the United States except the West and West‐North‐Central. The ERU was also found in larger cities with high population densities, whereas the Flat Fee, a SWU that charges a single rate for all properties, was found in smaller towns. Higher home values were correlated with higher monthly fees for 28% of the municipalities analyzed. The residential equivalence factor, a SWU that charges based on runoff produced, was popular in municipalities with higher home values, whereas the Flat Fee was popular in municipalities with lower home values. The number of SWUs established increased with Phase I municipal separate stormwater and sewer system (MS4) permit and Phase II small MS4 permit deadlines. Summary tables provide guidance to aid municipalities considering a SWU.